The development of an automated vehicle simulator for on-road study - Karjanto, Juffrizal; Md. Yusof, Nidzamuddin; Azmi, Mohd Shafiq Ikhwan; Hassan, Muhammad Zahir; Zulkifli, Abd Fathul Hakim; Mohamed Nazar, Mohamed Ihsan Sabri; Ab Rashid, Ahmad Azad; Mohd Jawi, Zulhaidi; Abu Kassim, Khairil Anwar (Society of Automotive Engineers, 2021)
In the current development of Automated Vehicle (AV) technology, one of the challenges yet to be resolved is when the AV is driving in urban environments. There will be mixed traffic scenarios where the AV and Vulnerable Road Users (VRU) such as pedestrians, cyclists, and motorcyclists, will share the road infrastructures. In this study, an AV simulator is developed and will be used to study the interaction between an AV and motorcyclist when they encounter a specific situation on the real roads. The study begins with developing a test vehicle based on the three main systems: the vehicle’s interior, outer appearance, and behavior. The vehicle’s interior comprises four subsystems: data acquisition, sensor, monitoring, and power management system. The outer appearance system has a look-alike LiDAR system, while the driving style sub-system monitors the behavior system. Future improvement will include developing ghost drivers to be implemented together with this system to enhance this on-road simulator's saliency.